👤

(3+3/5)^2-(3/5)^2-6•6/10

Răspuns :

Răspuns:

[tex]( 3 + \frac{3}{5} ) {}^{2} - ( \frac{3}{5} ) {}^{2} - \frac{6 \times 6}{10} [/tex]

[tex] \frac{324}{25} - \frac{9}{25} - \frac{18}{5} [/tex]

[tex] \frac{324}{25} - \frac{9}{25} - \frac{18 \times 5}{5 \times 5} = \frac{324 - 9 - 90}{25} = \frac{225}{25} = 9[/tex]

Sper că te-am ajutat!

Răspuns: [tex]\bf \red{\underline{~9~}}[/tex]

Explicație pas cu pas:

[tex]\bf \bigg(3+\dfrac{3}{5}\bigg)^2-\bigg(\dfrac{3}{5}\bigg)^2-6\cdot \dfrac{6^{(2}~}{10}=[/tex]

[tex]\bf \bigg(\dfrac{^{5)}3~}{1}+\dfrac{3}{5}\bigg)^2-\bigg(\dfrac{3}{5}\bigg)^2-6\cdot \dfrac{3}{5}=[/tex]

[tex]\bf \bigg(\dfrac{~15+3~}{5}\bigg)^2-\bigg(\dfrac{3^2}{5^2}\bigg)- \dfrac{~3\cdot 6~}{5}=[/tex]

[tex]\bf \bigg(\dfrac{18}{5}\bigg)^2-\dfrac{9}{25}- \dfrac{18}{5}= \bigg(\dfrac{18^2}{5^2}\bigg)-\dfrac{9}{25}- \dfrac{18}{5}=[/tex]

[tex]\bf \dfrac{324}{25}-\dfrac{9}{25}- \dfrac{18}{5}= \dfrac{~324-9~}{25}- \dfrac{18}{5}=[/tex]

[tex]\bf \dfrac{~315^{(5}~}{25}- \dfrac{18}{5}= \dfrac{63}{5}- \dfrac{18}{5}=[/tex]

[tex]\bf \dfrac{~63-18~}{5}= \dfrac{~45^{(5}~}{5}=\red{\underline{~9~}}[/tex]

==pav38==

Baftă multă !